Destination Management Organization –Destination Governance (DMODG) : Assistance in Papringan Village Tourism, Kaliwangi Village, Purwojati, Banyumas - Warto; Nike Mutiara Fauziah; Rindha Widyaningsih (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community Service entitled Destination Management Organization – Destination Governance (DMO-DG): Assistance in Papringan Tourism Village, Kaliwangi Village, Purwojati, Banyumas, aims to internalize the Tourism Awareness Movement (GSW) and Sapta Pesona in Papringan Tourism Village, Kaliwangi Village, Purwojati, Banyumas, Competence of tourism actors in managing Papringan Tourism Village, Kaliwangi Village, Purwojati, Banyumas can increase, Communities around tourist villages can be empowered, and the Tridharma of Higher Education can be realized through community service that focuses on Tourism Villages. There is great hope from the team for this service to achieve targets, including Increasing the Quality of Governance with the Destination Management Organization Model - Destination Governance (DMO-DG) in Papringan Tourism Village, Kaliwangi Village, Purwojati, Banyumas. The program is expected to benefit Institutional, Work Program, and Work Outcomes. Tourism Awareness Group has an integrated Tourism Village Management SOP. Papringan Tourism Village has excellent tour packages through tourism business training, tourism attractions, scouting, Outbound, and Edu tours so that it can sell 1000 packages tours in the long term. Through community empowerment with Asset Based Community Development (ABCD), the goals and targets can be achieved through this community empowerment program.